Neonatal blood TSH concentration in Wales (UK): an indicator of iodine sufficiency. (19th May 2014) - Evans, Carol; Barry Nix, Arthur; Hillier, Sharon; Moat, Stuart J.
Summary Objective Population iodine status can be assessed by urinary iodine concentrations, prevalence of goitre, frequency of newborn thyroid‐stimulating hormone (TSH) >5 mU/l and blood thyroglobulin concentrations. The UK population has historically been considered to be iodine sufficient; however, a recent survey of UK schoolgirls has demonstrated median urinary iodine concentrations consistent with mild iodine deficiency. The aim of our study was to assess the prevalence of TSH >5 mU/l in the newborn blood spot screening samples from the eligible population in Wales between 2011 and 2013 to assess iodine sufficiency. Measurements Blood spot TSH data for 104 992 infants during this time period were evaluated. Results The prevalence of TSH >5 mU/l in samples collected on days 4 and 5 of life were 1·5% and 0·9%, respectively. No increasing trend in blood spot TSH concentration was identified over the 3 years. Conclusions The distribution of blood spot TSH data from neonates in Wales has revealed no evidence to support the hypothesis that the population is iodine deficient. However, given that mild iodine deficiency has been reported in a cohort that will be childbearing in the next decade, we recommend that the distribution of neonatal blood spot TSH concentrations is monitored by the UK newborn screening programmes to identify any emerging trends in iodine status. Further studies to correlate maternal urinary iodine and newborn blood spot TSH are required to clarify the TSH cut‐off points associated with mild iodine deficiency relevant to the time of blood spot sampling in the UK.